Carbapenem resistance; surveillance data of 2013-2017 - Güven, Özlem; İstanbullu Tosun, Ayşe; Sever, Canan (Bulgarian Society for Microbiology (Union of Scientists in Bulgaria), 2018)
The aim of the study was to investigate the status of intestinal colonization with CRE in patients admitted to Istanbul Medipol University Hospital. CRE prevalence was found in 4.1% of specimens collected between January 2013 and August 2017. The results indicate that there was a peak in 2016 with an isolation rate of 6.9% that is thought to be associated with the increasing amount of foreign patients admitted to our hospital.

????? ?? ???????????? ? ?? ?? ???????? ???????? ?? ??????????? ?? ??????? ? ????????????????????? ???????? ?? ??? Enterobacteriaceae (CRE) ??? ????????, ?????? ? ???????????????? ??????? "???????" ? ????????. ?????????? ?????????? ?? CRE ? ?????????? ??? 4.1% ?? ???????, ??????? ????? ?????? 2013 ?. ? ?????? 2017 ?. ??????????? ????????, ?? ???? 2016 ?. ?? ???????? ??? ??? ?????? ?? ???????? 6.9%, ????? ???????? ? ???????? ? ???????????? ?????????? ???????????? ???????? ? ?????????.
Keywords: Carbapenem Resistance; Enterobactericeae; Intestinal Colonization